2023
DOI: 10.1097/icl.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics of 1976 Patients With Ectatic Corneal Disorders at a Single Center From 2010 to 2021: A Cross-Sectional Study of the Homburg Keratoconus Center

Abstract: Objectives: The study objective was to analyze the baseline characteristics of keratoconus (KC) patients at the Homburg Keratoconus Center from 2010 to 2021. Methods: This cross-sectional study included 3,674 eyes, with analysis of demographics, clinical findings, visual function, endothelial measurements, and topographic, tomographic, and corneal biomechanical data from the first visit. Results: Mean patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…It was shown that the most severe KC stage was set by parameter “B” followed by “E”, “A” and “C” [ 40 ]. As posterior elevation data and thinnest corneal thickness were diagnostic criteria in the selection of KC corneas for the study population used to create the BEST and also in Sideroudi's baseline HKC study [ 27 ], these are only frequency data and one cannot infer from this in principle that stages of “B” are generally more advanced than “E” or “A” in every KC [ 40 ]. The resulting BEST is meant to be an addition to the tomographic ABCD KC staging system that was published previously as it supplements biomechanical severity information for keratectasia.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the most severe KC stage was set by parameter “B” followed by “E”, “A” and “C” [ 40 ]. As posterior elevation data and thinnest corneal thickness were diagnostic criteria in the selection of KC corneas for the study population used to create the BEST and also in Sideroudi's baseline HKC study [ 27 ], these are only frequency data and one cannot infer from this in principle that stages of “B” are generally more advanced than “E” or “A” in every KC [ 40 ]. The resulting BEST is meant to be an addition to the tomographic ABCD KC staging system that was published previously as it supplements biomechanical severity information for keratectasia.…”
Section: Main Textmentioning
confidence: 99%
“…A baseline analysis of characteristics and application of the ABCD staging system on a large cohort of KC patients within the HKC revealed (1) more male (73%) than female (27%) KC patients, (2) more advanced posterior (“B”) than anterior (“A”) radius of curvature stages, (3) 8% to suffer from atopic dermatitis and 40% from allergies [ 20 ], (4) a mean ABCDE stage of A2B3C1D1E2 and (5) a mean Belin-Ambrósio deviation (BAD) index of 9.7 ± 8.7 among 3674 KC corneas [ 27 ].…”
Section: Introductionmentioning
confidence: 99%